Early Islam in Nusantara: The First Trace of Islam through the Spices Trade - Farid, Muhammad (Adabuna : Jurnal Pemikiran dan Pendidikan, 2021)
Abstract The history of the entrance of Islam became the most important and the most obscure event in the discourse of Indonesian history. The authors note two fundamental problems concerning this "Early Islam": terminological problems and geographical problems. By using structural approach and through the procedures of Heuristics, Source Criticism, Interpretation, and Historiography, the study found that Islam came to Banda-Maluku Islands since the first year of Hijri calendar, or between the 7th and 8th century, practiced by the nomadic Muslim travelers in several important cities, Banda and Ternate. Secondly, nutmegs and cloves were the main commodity trade that has captivated Muslim merchants to come to Banda Islands in the early period, thus, it made the region as the gate of Islam entrance in North Indonesia. Finally, the process of Islam institutionalization in the harbor cities such as Banda, Ternate, and Hitu reached its peak in the 13th and 14th century. This was evidenced by the changes of Kolano to Sultanate, the establishment of Islamic Confederation in Hitu and Banda, and the formation of OK (Orang Kaya, literally means “rich people”) “organization”—an organization of the rich people which regulated the trade issues. These findings are considered to make Banda Naira (Maluku) as the "new challenger" in the discourse of Early Islam in Indonesia. Keywords: Early Islam, Spices Trade, Nusantara